OCT ANGIOGRAPHY AND ITS ROLE IN THE STUDY OF RETINAL MICROCIRCULATION IN GLAUCOMA (PART ONE) - N. I. Kurysheva (Российский офтальмологический журнал)
There are two different points of view on the role of ocular microcirculation in glaucoma. According to one of them, ocular hemoperfusion reduction is a consequence of nerve tissue atrophy. Other authors suggest that the retinal microcirculatory bed can already be damaged at early stages of the disease, causing the death of neuronal structures. However, little is known today about retinal microcirculation in glaucoma. The introduction of optical coherence tomography angiography (OCTA) has opened prospects in understanding the connection of microcirculatory and structural damages in glaucoma. The paper provides the data on the anatomy and physiology of microcirculatory bloodstream of the retina and optic disc, which were obtained using OCTA. For citation: Kurysheva N.I. OCT angiography and its role in the study of retinal microcirculation in glaucoma (part one). Russian ophthalmological journal. 2018; 11 (2): 82-6. doi: 10.21516/2072-0076-2018-11-2-82-86 (In Russian).